Extraction of Iron from Aqueous Chloride Media in Presence of Aluminum - T. Mohammed, Wadood; Kh. Mageed, Alyaa (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
The extraction of iron from aqueous chloride media in presence of aluminum was studied at different kinds of extractants(cyclohexanone, tributyl phosphate, diethyl ketone), different values of normality (pH of the feed solution), agitation time, agitation speed, operating temperature, phase ratio (O/A), iron concentration in the feed, and extractant concentration]. The stripping of iron from organic solutions was also studied at different values of normality (pH of the strip solution) and phase ratio (A/O). Atomic absorption spectrophotometer was used to measure the concentration of iron and aluminum in the aqueous phase throughout the experiments.The best values of extraction coefficient and stripping coefficient are obtained under the conditions of operation given in the table below:System                     Operation       pH      Agitation Time(min.)      Agitation Speed(RPM)      TemperatureoC      Phase ratio      Cyclohexanone conc.cyclohexanone       exraction         1.5               10                                           400                                    30                           3/1                           50%                                  stripping            1                10                                           400                                    30                           3/1                           50%